Activating Mutation (V617F) in the Tyrosine Kinase JAK2 is Absent in Locally-Confined or Castration-Resistant Prostate Cancer - Lei Gu; Xian-Hua Zhu; Tapio Visakorpi; Kalle Alanen; Tuomas Mirtti; Tina Bocker Edmonston; Marja T. Nevalainen (Analytical Cellular Pathology)
Background: Transcription factor Stat5a/b is highly critical for the viability of human prostate cancer cells in vitro and for prostate tumor growth in vivo. Stat5 is constitutively active in clinical prostate cancers but not in the normal human prostate epithelium. Moreover, Stat5a/b activation in prostate cancer is associated with high histological grade of prostate cancer. However, the molecular mechanisms underlying constitutive activation of Stat5a/b in prostate cancer are unclear. The receptor-associated tyrosine kinase Jak2 is a known key activator of Stat5a/b in prostate cancer cells in response to ligand stimulation. Recently, a single gain-of-function point mutation of JAK2 was described in myeloproliferative diseases leading to constitutive Jak2 kinase activity, subsequent Stat5a/b activation and involvement of V617F Jak2 in the pathogenesis of myeloproliferative disorders.